The outcome of autologous stem cell transplantation in patients with plasma cell disorders and dialysis-dependent renal failure - Raab, Marc-Steffen; Breitkreutz, Iris; Hundemer, Michael; Benner, Axel; Klaus, Jens; Hegenbart, Ute; Möhler, Thomas; Ho, Anthony Dick; Zeier, Martin; Goldschmidt, Hartmut (Haematologica, the hematology journal, 2006)
Patients with multiple myeloma and end-stage renal failure on dialysis are frequently not considered eligible for high-dose therapy (HDT) due to higher transplant-related mortality (TRM). Our aim was to evaluate the toxicity and survival of dialysis-dependent patients after HDT with melphalan (100 mg/m(2)) compared to those of patients without renal insufficiency (melphalan 200 mg/m(2)) in a matched pairs analysis of 34 patients. No significant differences were observed between hematologic toxicity, TRM or disease response. Dialysis patients showed comparable event-free and overall survival. They required significantly extended intravenous antibiotic treatment and longer hospitalization. Thus, melphalan 100 mg/m2 is less toxic, yet equally efficient and improves the prognosis of this group of patients.
Gesehen am 09.11.2021
DOI fehlerhaft